Groups process and practice - Corey, Marianne Schneider 1942-; Corey, Gerald; Corey, Cindy (Australia Cengage Learning, 2018)
"This book outlines the basic issues and key concepts of group process and shows how group leaders can apply these concepts in working with a variety of groups. In many ways this is a 'how-to' book, but it is also a book about the 'why' of group leadership... this tenth edition...contains many subtle changes in our discussion of the topics within ech chapter, and many chapters have undergone considerable revision with new material added."--page xvii.
Introduction to group work: a multicultural perspective -- Group counselor -- Ethical and legal issues in group counseling -- Theories and techniques of group counseling -- Forming a group -- Initial stage of a group -- Transition stage of a group -- Working stage of a group -- Final stage of a group -- Groups in school settings -- Groups in community settings.
Keywords: Group psychotherapy; Group counseling; Group relations